Foudations of finance : The logic and practice of financial management - Keown, Arthur J.; Martin, John D.; Petty, J. William (Boston Pearson Education, 2011)
Contents: the scope and environment of financial management; the valuation of financial assets; investment in Long-Term assets; capital structure and dividend policy; working-capital management and international business finance.
Keywords: Tài chính - Ngân hàng